2005
DOI: 10.1073/pnas.0500519102
|View full text |Cite
|
Sign up to set email alerts
|

Barx2 functions through distinct corepressor classes to regulate hair follicle remodeling

Abstract: The hair-growth cycle, a complex biological system requiring coordinate alterations in gene expression and cellular behavior, provides a challenging model for investigating the interplay of specific transcriptional regulation events. Here we report that the Barx2 homeodomain factor serves as a regulator of hair follicle remodeling (catagen), and loss of Barx2 in mice causes a defect both in the initiation and progression of catagen, resulting in a protracted first catagen, and later, causing short hair in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
5
40
0
Order By: Relevance
“…At E16-16.5, Barx2 protein was detected in LGs by immunostaining (Fig. 1C,D) and by -galactosidase histochemistry in heterozygous Barx2-lacZ knock-in mouse embryos (Olson et al, 2005) (Fig. 1E).…”
Section: Barx2 Is Expressed In the Epithelial Component Of The Develomentioning
confidence: 99%
See 4 more Smart Citations
“…At E16-16.5, Barx2 protein was detected in LGs by immunostaining (Fig. 1C,D) and by -galactosidase histochemistry in heterozygous Barx2-lacZ knock-in mouse embryos (Olson et al, 2005) (Fig. 1E).…”
Section: Barx2 Is Expressed In the Epithelial Component Of The Develomentioning
confidence: 99%
“…-/-mice show eyelid fusion defects Barx2 -/-mice (Olson et al, 2005) showed multiple defects of ocular gland and eyelid development (Figs 2, 3). The development of mouse eyelids starts at E13.0-13.5, and complete eyelid closure is accomplished by E16.0-16.5.…”
Section: Barx2mentioning
confidence: 99%
See 3 more Smart Citations